(untitled) (Research, Society and Development, 2021)
The whitefly (Hemiptera: Aleyrodidae) represents a group of polyphagous sucking insects that make up the complex of pests that attack soybeans, having as main pest specie Bemisia tabaci (Gennadius, 1889). The objective of this research was to register the population fluctuation of Aleyrodidae in areas of corn and soybean cultivation in the municipalities of Currais and Bom Jesus-PI, to relate the occurrence of the pest with climatic factors and to investigate whether the Cerrado areas next to agricultural crops can serve as shelter from this pest in the region. Twelve collection points with yellow adhesive traps were defined. The average collection interval was 45 days, keeping the traps in the field for 24 hours. The indexes of diversity, equitability, dominance and frequency of the order Hemiptera and the family Aleyrodidae in the order Hemiptera were estimated. For Aleyrodidae graphs were drawn up correlating the occurrence with the weekly precipitation accumulated prior to collection. The Aleyrodidae family is more dominant and frequent in soybean cultivation area when compared to the corn cultivation area; the population of Aleyrodidae tends to decrease with increasing precipitation; in areas of soy and corn cultivation continuous to the Cerrado area the population of Aleyrodidae tends to be concentrated in the Cerrado forest; the maintenance of Cerrado areas close to the soybean and corn cultivation areas can favor the integrated management of the family Aleyrodidae and decrease the risks of population outbreaks in the commercial cultivation areas.